Analysis of interactions of clinical mutants of catalase-peroxidase (KatG) responsible for isoniazid resistance in Mycobacterium tuberculosis with derivatives of isoniazid. (December 2017) - Unissa, Ameeruddin Nusrath; Doss C., George Priya; Kumar, Thirumal; Swathi, Sukumar; Lakshmi, Appisetty Ramya; Hanna, Luke Elizabeth
Highlights: Mutations at codon 315 in katG are the major cause of isoniazid (INH) resistance in Mycobacterium tuberculosis (MTB). Study of the binding interaction of all naturally occurring KatG mutants of MTB at position 315 with derivatives of INH. Compound C50 produced a high score with wild-type (WT) KatG and three mutants (S315T, S315I and S315R). C50 exhibited minimal deviation and fluctuation with WT and 3 KatG mutants and may be a good lead for INH-resistant MTB. This information will aid lead-based identification of INH derivatives that may be used against INH-resistant MTB strains. Abstract: Objectives: Isoniazid (INH) resistance is a major contributor to the emergence of multidrug resistance in Mycobacterium tuberculosis (MTB), hampering the success of tuberculosis treatment. This study aimed to identify good leads based on INH derivatives against INH-resistant MTB strains. Mutations at codon 315 in the katG gene encoding catalase-peroxidase (KatG) are the major cause of INH resistance in MTB. The most prevalent substitution is S315T; other substitutions include S315I, S315R, S315N and S315G. Methods: In this study, all five naturally occurring mutants (S315T, S315I, S315R, S315N and S315G) of KatG were docked and simulated with 50 INH derivatives in comparison with the wild-type (WT) KatG. Results: The docking results suggested that compounds C30, C45 and C50 gave the highest scores when bound to the mutants of KatG. Of note, C50 produced a high score with the WT as well as with three mutants (S315T, S315I and S315R). Simulation studies indicated that C50 exhibited minimal deviation and fluctuation between WT and three mutants compared with C30 and C45, which displayed significant changes with WT and the S315N and S315G mutants, respectively. Conclusions: C50 can be considered as a better lead for INH-resistant strains. These models demonstrate the binding interaction of all naturally occurring KatG mutants of MTB at position 315 with derivatives of INH. This information will be helpful for lead compound-based identification of derivatives that may be used against INH-resistant MTB strains and may provide a useful structural framework for designing new antitubercular agents that can circumvent INH resistance.